If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 36m + 107 + -3m = 36 Reorder the terms: 107 + 36m + -3m = 36 Combine like terms: 36m + -3m = 33m 107 + 33m = 36 Solving 107 + 33m = 36 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-107' to each side of the equation. 107 + -107 + 33m = 36 + -107 Combine like terms: 107 + -107 = 0 0 + 33m = 36 + -107 33m = 36 + -107 Combine like terms: 36 + -107 = -71 33m = -71 Divide each side by '33'. m = -2.151515152 Simplifying m = -2.151515152
| (x-4)+(2x-7)=0 | | 8m=-3m+1 | | V-2x+3y-z=8 | | 0=-15-3y-4x | | 5p-9=2p+21 | | (X+8)=(4X-28) | | 2.5(2+z)=5(z+2.5) | | y=1.5-1 | | A=6F+4g | | 5x-2(7x-1)=14x | | 4Y^2+x^2=4 | | 3a-2=5 | | 4Y^2+x^2= | | 7(X-5)=71 | | 35x+7=11x+4 | | 4z=6z+2 | | Logx=2.4 | | 2x-4y+z=0 | | 8(2z-5)=4n+8 | | 3-8+2x=11+6x | | p/20=8/4 | | [-2+6x]+3=59 | | 5.79x-3.14y=-13.54 | | 3(2-0.9q)+(-1.3h-4)= | | -3(4t-4)+6t=5t-9 | | x^2+8+14=0 | | 4x-10+2x=8 | | f+g=f+h | | x^2+814=0 | | x^2+8+14= | | 6-(-5r)=5r+6 | | -8x+32-5=-5-9x |